Terrestrial laser scanning assisted flatness quality assessment for two different types of concrete surfaces. (15th March 2020) - Li, Dongsheng; Liu, Jiepeng; Feng, Liang; Zhou, Yang; Liu, Pengkun; Chen, Y. Frank
Highlights: Automatic flatness inspection of construction and component surfaces is presented. A color coded deviation map is proposed for the visualization of flatness information. High deviations often occur near the edges of construction surface. Abstract: Terrestrial laser scanning (TLS) that can acquire reliable scanned data with high-precision, has been popularly adopted for the flatness quality assessment (FQA) in civil engineering. However, existing TLS assisted FQA methods are all designed particularly for a certain type of surfaces, like construction surfaces and component surfaces. To the best of our knowledge, no existing method that can be applied to both types of surface data and provide a visual representation of the flatness information. Keeping these in mind, based on TLS, this study develops a practical and general approach for the FQA of concrete surfaces, which can be applied for the two different types of scanned objects. A color coded deviation map is also developed to represent the FQA result. Validation experiments are conducted on a constructed room and on two full-scale precast concrete components, which indicate that the proposed approach is convenient and practical.